Sensory Reportage and the 'Steeplechase' Between Novels and Newspapers in Verne's Michel Strogoff. (2nd October 2017) - Rees, Kate
ABSTRACT: This article considers the emphasis on acute sensory perception associated with the rise of the 'grand reporter' in the late nineteenth century, and the representation of such perception in the novels of Jules Verne in particular. Focusing in particular on Verne's novel Michel Strogoff (1876), I discuss the comic exaggeration of the visual and aural capacities of the reporters depicted in this text, arguing that the subversion of sensory experience acts as a riposte to practices of information-gathering associated with the new media, such as the eyewitness report, and also as a reflection on techniques of realist literature. The article draws on discussion of the senses and the critique of ocularcentrism in particular in anthropological studies, suggesting that Verne's Michel Strogoff offers a satire of reifying practices of viewing the world, and instead implies the need for a multi-sensorial approach to representing the real.